Analysis and sensitivity study of steam explosion loads - Wei, Linkai; Meignen, Renaud; Picchi, Stéphane; Rimbert, Nicolas (Annals of nuclear energy, 2023)
•A detailed analysis of the steam explosion characteristics is performed with the MC3D software.•A comprehensive review of the up-to-date knowledge and modeling issues is given.•1-D steam explosion calculations are performed with sensitivity of melt and void fractions.•The impacts of major modeling uncertainties are discussed. Steam Explosion is a destructive event that may arise from the mixing of the molten fuel (corium) with the liquid coolant (water, sodium) during the course of a severe accident. Due to its high complexity and very specific related conditions, the phenomenon is still subject to numerous uncertainties. MC3D is a CFD software for the simulations of 3D multiphase flows and is used to evaluate steam explosion loads through a specific application called EXPLO. The present paper provides a comprehensive analysis of the characteristics of steam explosion, as computed with MC3D-EXPLO, using a simple one-dimensional test case. The ultimate goal is to better understand the behavior of the code itself in order to give orientations for improvements. An in-depth analysis of the current knowledge and main points of modeling is at first provided, highlighting the major uncertainties. The analysis of pressure shock propagation in two-phase liquid/gas flows is then performed. It allows to propose an explanation of the difficulties encountered to obtain strong explosions with UO2/ZrO2 melts from a distant trigger in one-dimensional geometries such as in the KROTOS installation. The general cases of 3-phase flows are then examined with details, as a function of the melt and vapor volume fractions. A comparison of the behavior with the classical analytical detonation model is given and the competition between the fragmentation and heat transfer in terms of time scales is outlined. Finally, the impact of major modeling issues are discussed and conclusions are provided for recommendations of improvements.